Oleic acid derivative of polyethylenimine-functionalized proliposomes for enhancing oral bioavailability of extract of Ginkgo biloba. (3rd May 2016) - Zheng, Bin; Yang, Shuang; Fan, Chunyu; Bi, Ye; Du, Lin; Zhao, Lingzhi; Lee, Robert J.; Teng, Lesheng; Teng, Lirong; Xie, Jing
Abstract: The present systematic study focused to investigate the oleic acid derivative of branched polyethylenimine (bPEI-OA)-functionalized proliposomes for improving the oral delivery of extract of Ginkgo biloba (GbE). The GbE proliposomes were prepared by a spray drying method at varying ratios of egg yolk phosphatidylcholine and cholesterol, and the optimized formulation was tailored with bPEI-OA to obtain bPEI-OA-functionalized proliposomes. The formulations were characterized for particle size, zeta potential, and entrapment efficiency. The release of GbE from proliposomes exhibited a sustained release. And the release rate was regulated by changing the amount of bPEI-OA on the proliposomes. The physical state characterization studies showed some interactions between GbE and other materials, such as hydrogen bonds and van der Waals forces during the process of preparation of proliposomes. The in situ single-pass perfusion and oral bioavailability studies were performed in rats. The significant increase in absorption constant ( K a ) and apparent permeability coefficient ( P app ) from bPEI-OA-functionalized proliposomes indicated the importance of positive charge for effective uptake across the gastrointestinal tract. The oral bioavailability of bPEI-OA-functionalized proliposomes was remarkable enhanced in comparison with control and conventional proliposomes. The bPEI-OA-functionalized proliposomes showed great potential of improving oral absorption of GbE as a suitable carrier.